The Multiscale TROPIcal CatchmentS critical zone observatory M‐TROPICS dataset I: The Nyong River Basin, Cameroon - Audry, Stéphane; Ateba Bessa, Henriette; Bedimo Bedimo, Jean‐Pierre; Boeglin, Jean‐Loup; Boithias, Laurie; Braun, Jean‐Jacques; Dupré, Bernard; Faucheux, Mikael; Lagane, Christelle; Maréchal, Jean‐Christophe; Ndam‐Ngoupayou, Jules Remy; Nka Nnomo, Bernadette; et al. (Hydrological processes, 2021)
Simultaneously acquiring time series of climate, hydrology and hydrochemical data over decades on river systems is pivotal to understand the complex interactions involving rock, soil water, air and biota in the Critical Zone, to build integrated modelling and to propose predictive scenarios. Among the Critical Zone Observatories (CZOs) implemented in the past 25 years, only a few are located in the humid Tropics despite the importance of these regions in terms of population density, fast‐changing land use, biodiversity hotspots, biomass stock on continents, size of river systems, etc. Since 1994, weathering and erosion processes and fluxes have been investigated at both local (experimental watershed) and regional scales in the Nyong River Basin (Cameroon) which belongs to the Critical Zone Observatories network named Multiscale TROPIcal CatchmentS (M‐TROPICS). The data shared by M‐TROPICS in Cameroon are: (1) rainfall; (2) air temperature, air relative humidity, wind speed and direction, and global radiation; (3) stream and river water level; (4) pH, electrical conductivity, water temperature and suspended particulate matter (SPM) concentration; (5) major ion, alkalinity and dissolved organic carbon (DOC) concentrations. The dataset already contributed to describe the water partitioning in these tropical humid watersheds, to better understand the factors controlling chemical weathering and physical erosion in tropical ecosystems, particularly the role of organic matter. The dataset also contributed to calculate elemental weathering fluxes and saprolite production rate and to propose denudation rates on tropical cratonic landscapes. Hydrological modelling allowed quantification of the geographical water sources contributing to streamflow. DOC data were used to determine greenhouse‐gas emissions and carbon budgets from African inland waters. However, long‐term solute concentrations at the outlet of a small tributary of the Nyong River exhibit non‐stationary behaviour over the last 26 years. The processes governing those fluctuations are not yet fully understood and might be related to changes in the hydrological regime, land‐cover and land‐use. The latter highlights the need for longer time‐series and continued support for CZOs particularly in the humid tropics. Since 1994, weathering and erosion processes and fluxes have been investigated at local (experimental watershed) and regional scales in the Nyong River Basin (Cameroon) which belongs to the CZO network M‐TROPICS. The data shared by M‐TROPICS in Cameroon are: (1) rainfall; (2) air temperature, air relative humidity, wind speed and direction, and global radiation; (3) stream and river water level; (4) pH, electrical conductivity, water temperature and suspended particulate matter concentration; (5) major ion, alkalinity and dissolved organic carbon concentrations.